Abrocitinib Treatment in Diffuse Alopecia Areata: A Case Report and a Literature Review - Xiaojing Zhang; Jianbo Zhong; Liming Wu; Ping Yang; Xingyun Zhao; Yingzhi Luo; Yunmi Qiu (Clinical Case Reports, 2026)
ABSTRACT Alopecia areata is an autoimmune disease with diverse clinical manifestations. This case report describes a patient with diffuse alopecia areata who responded well to oral abrocitinib, resulting in complete hair regrowth. The patient achieved complete recovery without any observed adverse effects.